RISKS OF DEVIANCE AND SOCIAL SECURITY OF YOUTH - T. V. Shipunova (Дискурс)
Since deviance of youth is a result of certain life circumstances and social disadvantage, the author proposes to consider the risks of youth deviance through the prism of social security / protection of this social group. Social injustice is considered as a generalized (general) social risk of deviance. The reasoning of the author is supported by statistical data about certain types of youth deviance, as well as data about the level of social security / protection of young people.